Analysis of p53- immunoreactivity in astrocytic brain tumors. - T. V. Shinkarenko; I. S. Shpon‘ka (Medičnì Perspektivi)
P53 is an antioncogene with the frequently occured mutations in human tumor cells, leading to corresponding protein overexpression which can be detected by immunohistochemistry. Researches dedicated to the investigation of possibilities of using this technique gave controversial results. The authors investigated features of p53 protein expression in astrocytic brain tumors with different degrees of malignancy. Analyzed the relationship of the expression level of p53 by tumor cells with clinical parameters and Ki-67 proliferation index (PI) as well. Tissues were collected from 52 cases with diagnosed astrocytic brain tumors. The sections were immunohistochemically stained with p53 and Ki-67. For each marker, 1000 tumor cells were counted and the ratio of positive tumor cells was calculated using software package ImageJ 1,47v. In normal brain tissue p53- expression was not identified. p53-immunoreactive tumor cells were detected in 25% (1/4) pilocytic astrocytomas, 33.3% (2/6) of diffuse astrocytomas, 53.8% (7/13) anaplastic astrocytomas, 58.6% (17/29 ) glioblastomas. A high proportion of p53-immunoreactive cells (> 30%) was observed only in glioblastomas. The level of p53-imunoreactivity was not related to the age, gender and Grade WHO (ρ> 0,05). Spearman correlation coefficient between the relative quantity of ki-67- and p53-immunoreactive nuclei showed weak direct correlation (0.023), but the one was not statistically significant (ρ> 0,05). The level of p53-imunoreactivity is not dependent from age and sex of patients, Grade (WHO) and proliferative activity (p>0,05) but the high level of p53-immunoreactive cells (>30%) is found in glioblastoma specimens only, that may be due to the accumulation of mutations in DNA of tumor cells. There is insignificant weak relationship between relative quantities of ki-67- and p53-immunoreactive tumor cells (ρ>0,05).